1994
DOI: 10.1007/bf02098391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of benzoic and cinnamic acids on growth, mineral composition, and chlorophyll content of soybean

Abstract: Organic acids are major water-soluble allelochemicals found in soil infested with quackgrass and are involved in several processes that are important in plant growth and development. This study was carried out to gain more information on the effects of benzoic acid (BEN) andtrans-cinnamic acid (CIN) on growth, mineral composition, and chlorophyll content of soybean [Glycine max (L.) Merr. cv. Maple Bell] grown in nutrient solution. The two allelochemicals reduced root and shoot dry biomass of soybean. Treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 30 publications
4
49
0
4
Order By: Relevance
“…NO promoted root growth singly and in combination. BA inhibits root elongation and formation of secondary roots (Baziramakenga et al 1994). BA might have interrupted the meristematic activity of root causing impaired cell division (Vaughan & Ord 1991) or hormonal imbalance (IAA) which affected growth (Rice 1984).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NO promoted root growth singly and in combination. BA inhibits root elongation and formation of secondary roots (Baziramakenga et al 1994). BA might have interrupted the meristematic activity of root causing impaired cell division (Vaughan & Ord 1991) or hormonal imbalance (IAA) which affected growth (Rice 1984).…”
Section: Resultsmentioning
confidence: 99%
“…Benzoic acid (BA) and its derivatives are reported in plant and soil (Rice 1984;Vaughan & Ord 1991;Baziramakenga et al 1995). BA in excess amount inhibits SG and seedling growth (Maffei et al 1999), decreases respiration and photosynthesis by inhibiting electron transport (Zhou et al 2006), affects chlorophyll biosynthesis and protein content (Baziramakenga et al 1994), and interferes with sugar metabolism and nitrate reductase (NR) activity in several crop plants (Naguib 1965;Robert et al 1982). It causes membrane damage by inducing electrolyte leakage and lipid peroxidation (LP) (Baziramakenga et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting anatomical and morphological distortion delaying seed germination, inhibits germinal root elongation, and lead to their dying off (Rice, 1984). Disorganisation in the functioning of cells, tissues and 259 physiological processes leads to lack of root hairs formation, lateral roots and trend of roots to the horizontal growth which are results of direct contact root with allelopathic substances (Baziramakenga et al, 1994). The morphogenetic changes are the results of influence allelopathic substances which ultimately affects the size and quality of plants (Lyu and Blum, 1990;Skrzypek et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Cruz et al [49] investigated the effect of allelochemicals on the P. vulgaris root where root tip cells were extruded together and that cell organization was disordered with little cell differentiation Batish et al [27] reported that the activity proteases in hypocotyl cuttings of P. aureus decreased significantly when to the caffeic acid was treated as allelochemical. Baziramakenga et al [23] studied the effects of benzoic acid and trans-cinnamic acid on growth, mineral composition, and chlorophyll content of soybean G. max grown in nutrient solution. These allelochemical showed negative effects on G. max by altering ion uptake and transport, and by reducing chlorophyll content.…”
Section: Allelochemical Mechanismmentioning
confidence: 99%
“…Baziramakenga et al [23] studied the effects of benzoic acid and trans-cinnamic acid on growth of G. max (L.) grown in nutrient solution. The two allelochemicals reduced root and shoot dry biomass of soybean.…”
Section: Introductionmentioning
confidence: 99%